HUBUNGAN KUALITAS PELAYANAN KEPERAWATAN DENGAN TINGKAT KEPUASAN PASIEN PESERTA JAMKESMAS DI IRINA E BLU RSUP PROF. Dr. R. D. KANDOU MANADO - Vera A. Hermanus (POLTEKKES KEMENKES MANADO, 2013)
The quality of nursing service is proffesional attitude from the nurse giving comfortable feel to the patient who follow the recovery treatment. Jamkesmas is a government program to increase the quality service and the satisfaction from under society but the reality shows that not all society who use jamskesmas satisfaction with its, that all because they feel the server attitude lack of friendly, lack of communicative, and there are the different service between the patient in first class and the member of jamkesmas.The aim of this research is to know the correlation between a nursing service quality with satisfaction level from the jamkesmas member patient in the Irina E Blu prof. Dr. R.d. Kandou hospital Manado. This research is analitic survey with cross sectional. The all populations are the patients parents whose members of jamkesmas and have been treated in hospital at least 3 days, they are 35 peoples that accept to be the responder.The sampling technique use purposive sampling and the data were analyzed by SPSS program 17 version with Chi-square. The result show that the statistic analysis for acception, attention, communication, relation, and responsibility are Ho refused and Ha accepted it mean that there are relations between acception, attention, communication, relation, and responsibility with the level of satisfaction from the parents of patients who follow jamskesmas program.The conclusion is a nursing service quality has relation with satisfaction level from the jamkesmas member patient in the Irina E BLU Prof. Dr. R.D. Kandou Hospital Manado